Mapping of Agriculture Knowledge Information System for Betel Vine Growers - Biswas, Manaranjan; Saha, Anindita (International Journal of Economic Plants, 2020)
Studying Agriculture Knowledge Information System (AKIS) in terms of generation, dissemination, transformation, utilization, storage and retrieval of knowledge and information is needed for Agriculture development. Study was conducted in purposively selected Nadia district of West Bengal. Betel vine growers, extentionists and researchers were considered as respondents. Information obtained from all the actors of AKIS was summarized in matrix from to analyze the extent of information exchange among various actors pertaining to cultural practices, plant protection techniques and harvesting of betel vine cultivation. The matrix revealed that information flow was linear in majority of the cases. The feedback got blocked with some of the actors, as upstream flow of information was weak. The present study was undertaken to study the existing Farmer-Extensionists-Researcher linkage as perceived by the linkage matrix with AKIS. A total of 200 farmers responding Karimpur 1, Karimpur 2, Krishnaganj and Chakdah block of Nadia district were selected for the study. The district and blocks were selected purposively for the study. Farmers were selected by the simple random sampling method. The result of the study reveal that betel growers had low linkage with researcher and were found maximum linkage with extension workers like Assistant Director of Agriculture, Krishi Projukti Sohaok, Opinion leaders, Dealers etc.